The die swell eliminating mechanism of hot air assisted 3D printing of GF/PP and its influence on the product performance - Yang Ru; Xiao Jianhua; Liu YingLan; Xu ShiKang (e-Polymers, 2024)
For eliminating the die swell phenomenon in 3D printing of GF/PP, a hot air assisted 3D printing method is proposed and its mechanism is studied. A two-phase flow model consisting of compressible gas and in-compressible melt is established, and the process of polymer filament extrusion is simulated. A series of experiments are conducted to compare the differences between traditional printing and gas-assisted printing in terms of extruded filament, temperature, and morphology. The simulation and experiment results show that the addition of gas effectively mitigates the melt die swell, and increases the extrusion filament temperature to more than 70°C. The extrusion pressure is reduced about two orders of magnitude, and the first normal stress is decreased from 400,000 to 20,000 Pa. The surface morphology of printed product is smoother and more refined. This study provides valuable information for understanding the principles of gas-assisted printing and demonstrates its potential for improving printing quality and efficiency.